Effect of media and environmental factors on growth and cellulase production by microporus xanthopus - Ramapraba., Appanna, (Universiti Malaysia Sarawak (UNIMAS), 2004)
Microporus xanthopus obtained from peat swamp forest at University Malaysia Sarawak (UNIMAS) was identified. Effects of media and environmental factors on growth of M. xanthopus were studied. M. xanthopus was grown on potato dextrose agar (PDA), potato carrot agar (PCA) and malt extract agar (MEA) at room temperature. This fungus grew significantly faster, at P=O.OS on PDA compared to growth on PCA or MEA The effect of light on growth of M. xanthopus was studied by growing this fungus on PDA in light and dark condition at room temperature. The fungus grew significantly faster, at P=O.OS in dark condition after 96 hours of incubation. The effect of temperature was studied by growing M. xanthopus on PDA and incubated at lSoC, 20°C, 2SoC, 30°C and 3S°C, in dark condition. Optimum growth was obtained at 30°C and no growth was recorded at 3S°C. The effect of pH was studied by growing M. xanthopus in potato extract broth (PDE) and incubated at 30°C in dark condition. The pH of the media used were; S.O, 6.0,6.5, 7.0, 8.0 and 9.0. The highest average mycelium dried weight of the fungus was obtained at pH 6.0. Study on cellulase production of the fungus was carried out by conformation test on carboxylmethycellulose (CMC) media and growth on B-V11 medium. Effect of concentrations of nitrogen sources (NH4)2S04, yeast extract and KN03 on cellulase activity in shake-flask cultures was also observed. Cellulase activity was determined using dinitrosalicylic acid (DNS) enzyme assay and protein content was determined using Bradford protein assay. Yeast extract, 6g!l, gave the highest value of cellulase specific activity (0.98IlmoVmin/mg) on day 6. This fungus was able to produce cellulase in media contain all the nitrogen sources except (N~hS04.